2019
DOI: 10.1016/j.microc.2019.03.059
|View full text |Cite
|
Sign up to set email alerts
|

Phenolic acids, cinnamic acid, and ergosterol as cosmeceutical ingredients: Stabilization by microencapsulation to ensure sustained bioactivity

Abstract: The global cosmetic industry is constantly searching for new ingredients with multifunctional properties. In this context, phenolic compounds (p-hydroxybenzoic, p-coumaric, and protocatechuic acids), cinnamic acid and ergosterol were evaluated for their anti-inflammatory, anti-tyrosinase and antimicrobial activities, and thereafter microencapsulated by the atomization/coagulation technique. After characterization (morphology, particle size distribution and encapsulation efficiency), the microencapsulated compo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(29 citation statements)
references
References 36 publications
0
28
1
Order By: Relevance
“…These phenolic acids are used as precursors in the synthesis of lignins and other phenolics [136]. Taofiq et al [156] conducted a study on individual compounds as possible ingredients in cosmeceutical formulations. The authors concluded that p-coumaric, protocatechuic, and cinnamic acids displayed anti-tyrosinase, antimicrobial, and anti-inflammatory activities, showing their potential for the cosmeceutical industry.…”
Section: Polyphenols As Extracted Biocompoundsmentioning
confidence: 99%
“…These phenolic acids are used as precursors in the synthesis of lignins and other phenolics [136]. Taofiq et al [156] conducted a study on individual compounds as possible ingredients in cosmeceutical formulations. The authors concluded that p-coumaric, protocatechuic, and cinnamic acids displayed anti-tyrosinase, antimicrobial, and anti-inflammatory activities, showing their potential for the cosmeceutical industry.…”
Section: Polyphenols As Extracted Biocompoundsmentioning
confidence: 99%
“…The ability of compound 46 to inhibit tyrosinase was credited to its ability to reduce microphthalmia-associated transcription factor (MITF) [77] and tyrosinase mRNA expression as high as 73% and 82%, respectively. The results showed that compound 46 has the potential to be used together with other bioactive ingredients for protection against hyperpigmentation [76]. Gunia-Krzyzak et al reported compound 46-containing cream that decreased erythema and pigmentation when applied daily on the foreskin arm [78].…”
Section: Cinnamic Acid Derivatives With Antioxidant and Anti-inflammamentioning
confidence: 99%
“…Its anti-inflammatory activity was measured to be EC 50 of 152 µg/mL and anti-tyrosinase activity of EC 50 ˃ 2.0 mg/mL. [ 76 ]. The ability of compound 46 to inhibit tyrosinase was credited to its ability to reduce microphthalmia-associated transcription factor (MITF) [ 77 ] and tyrosinase mRNA expression as high as 73% and 82%, respectively.…”
Section: Cinnamic Acid Derivatives With Antioxidant and Anti-inflamentioning
confidence: 99%
“…Such positive effects were correlated with antioxidant and anti-tyrosine activities [ 119 ]. Phenolic acids, namely p -hydroxybenzoic, p -coumaric, and protocatechuic acids, showed stable bioactivities, e.g., antioxidant, anti-tyrosinase, and anti-inflammatory effects, when added in a cosmetic cream base [ 120 ].…”
Section: Potential Applications—food and Cosmetic Industries And Ementioning
confidence: 99%